2018
DOI: 10.1093/rap/rkx019
|View full text |Cite
|
Sign up to set email alerts
|

What does evidence-based medicine tell us about treatments for different subtypes of psoriatic arthritis? A systematic literature review on randomized controlled trials

Abstract: Objective PsA is a heterogeneous disease with various subtypes of joint manifestations, which can affect the homogeneity of randomized controlled trials (RCTs). The aim of this systematic literature review was to evaluate the inclusion criteria, demographics and outcomes of RCTs to see whether the whole spectrum of PsA was represented. Methods Medline, EMBASE and Cochrane databases were screened for RCTs on the efficacy of any treatment for PsA up to 4 October 2016 to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The clinical trials use the commonly accepted definitions of these phenotypes, which have shown significant discrepancies with imaging modalities. For example, the vast majority of the clinical trials have only been focusing on the effectiveness of therapies on polyarticular phenotype in PsA, with few to none data on the axial disease, clinical enthesitis, or dactylitis as a primary outcome [52]. The efficacy data on features such as enthesitis or dactylitis has mostly been exploratory.…”
Section: Better Phenotyping Patients In Clinical Practice and Trialsmentioning
confidence: 99%
“…The clinical trials use the commonly accepted definitions of these phenotypes, which have shown significant discrepancies with imaging modalities. For example, the vast majority of the clinical trials have only been focusing on the effectiveness of therapies on polyarticular phenotype in PsA, with few to none data on the axial disease, clinical enthesitis, or dactylitis as a primary outcome [52]. The efficacy data on features such as enthesitis or dactylitis has mostly been exploratory.…”
Section: Better Phenotyping Patients In Clinical Practice and Trialsmentioning
confidence: 99%
“…In the studies selected for the SLR, the rate of PsA patients with axial disease was generally low (< 15%) [95]. Specific sub-analyses of axial manifestations were often lacking, although some positive evidence for tofacitinib [96] or ustekinumab [97] is available.…”
Section: Evidencementioning
confidence: 99%
“…Symptoms of MBP often worsen with movement and exercise and appear to correlate with injury and more acute onset [ 26 ]. Typically, its insidious onset occurs at an older age than IBP and can be acute or chronic [ 27 , 79 ].…”
Section: Differential Diagnosis Of Ibp Versus Mbpmentioning
confidence: 99%